Cardiac magnetic resonance for the risk stratification of heart transplant recipients: ready for prime time? - Hofmann, Nina P.; Katus, Hugo A.; Korosoglou, Grigorios (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
With great interest we read the study of Butler et al. (1) entitled ‘Cardiovascular MRI predicts 5-year adverse clinical outcome in heart transplant recipients’, which was recently published in the American Journal of Transplantation. Over a long follow-up duration (4.9 yrs) the authors demonstrated that the evaluation of cardiac magnetic resonance imaging (CMR) parameters is useful for the prediction of outcomes in heart transplant (HT) recipients. In this regard, myocardial scar assessed by late gadolinium enhancement (LGE) and right ventricular end-diastolic volume index (RVEDVI) were independently associated with cardiac death and hospitalization due to cardiac symptoms. Based on these results, the authors suggest that prognostic models should not only include clinical and demographic variables as recommended by the international society of heart and lung transplantation (ISHLT) (2), but also consider CMR imaging parameters. In this regard, the versatility of CMR allows for the noninvasive and reproducible assessment of cardiac anatomy, deformation and function, perfusion, viability and if required metabolism and tissue characterization without radiation exposure for the patients (3).